The Utilization of Social Media in the State Islamic Universities in Indonesia - Muhammad Munadi; Fauzi Annur (IAIN Ponorogo, 2021)
This study aims to determine the trend of followers of each social media and the use of social media at four State Islamic Universities (UIN) in Indonesia. This study used a content analysis approach with data from websites. These documents could be downloaded from websites related to social media. The sample taken was four UIN which have relatively active social media in updating. Data validity was done by validating data internally as well as cross-data. The data analysis used interactive analysis and descriptive statistical analysis. Moreover, the results showed that the use of social media was varied. Facebook and Instagram were for academic activities, including promotion for prospective new students. It dominantly occurs in all research locations and is balanced with the content of national and religious activities. Penelitian ini bertujuan untuk mengetahui trend followers masing-masing media sosial, serta penggunaan media sosial di 4 Perguruan Tinggi Islam Negeri (UIN) di Indonesia yang fokus pada masing-masing pulau satu UIN. Penelitian ini menggunakan pendekatan analisis isi dengan data dari website berupa dokumen yang dapat diunduh dari website yang berhubungan dengan media sosial. Sampel yang diambil adalah 4 UIN yang memiliki media sosial yang relatif aktif melakukan update. Validitas data dilakukan dengan validasi data secara internal maupun data silang. Analisis data menggunakan analisis interaktif dan analisis statistik deskriptif. Hasil penelitian menunjukkan bahwa penggunaan media sosial bervariasi, di Facebook dan Instagram untuk kegiatan akademik termasuk promosi untuk calon mahasiswa baru dominan terjadi di semua lokasi penelitian dan diimbangi dengan konten ucapan kegiatan nasional dan keagamaan.